2020
DOI: 10.1016/j.stemcr.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Human Stem Cell Resources Are an Inroad to Neandertal DNA Functions

Abstract: Summary Induced pluripotent stem cells (iPSCs) from diverse humans offer the potential to study human functional variation in controlled culture environments. A portion of this variation originates from an ancient admixture between modern humans and Neandertals, which introduced alleles that left a phenotypic legacy on individual humans today. Here, we show that a large iPSC repository harbors extensive Neandertal DNA, including alleles that contribute to human phenotypes and diseases, encode hundre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Many issues are epistemological, including the fact that the cognition of extinct hominin species cannot be directly assessed and valid model organisms for these species are currently non-existent (cf. Breyl 2020; Michlich 2018: 7; Putt et al 2017: 1; but see Dannemann et al 2020;Trujillo et al 2021). Fortunately, however, the small number of previous experimental studies provide a valuable, albeit only fragmentary picture of how Palaeolithic-stone-tool-related behaviors are associated with modern brain and cognitive functioning.…”
Section: Previous Experimental Studiesmentioning
confidence: 99%
“…Many issues are epistemological, including the fact that the cognition of extinct hominin species cannot be directly assessed and valid model organisms for these species are currently non-existent (cf. Breyl 2020; Michlich 2018: 7; Putt et al 2017: 1; but see Dannemann et al 2020;Trujillo et al 2021). Fortunately, however, the small number of previous experimental studies provide a valuable, albeit only fragmentary picture of how Palaeolithic-stone-tool-related behaviors are associated with modern brain and cognitive functioning.…”
Section: Previous Experimental Studiesmentioning
confidence: 99%
“…It remains to be seen how successful these approaches are at predicting archaic human phenotypes. A possible inroad into validation could rest on functional assays for testing and evaluating the phenotypic impact of archaic DNA ( Dannemann et al, 2020 ; Dannemann and Gallego Romero, 2021 ; Trujillo et al, 2021 ).…”
Section: Inferring Complex Traits In Archaic Hominidsmentioning
confidence: 99%
“…Considering the high number FIGURE 2 | Addressing the neurobiology of recent human history using iPSCs. Human pluripotent stem cells (iPSCs) carrying natural or introduced (via CRISPR-Cas9 genome editing) Neandertal or Denisovan ancestry can be differentiated into various 2D-cell systems and 3D-organoids types to generate "ancestralized" cells and tissues like brain, lung, liver, heart, pancreas, and intestine (Dannemann et al, 2020).…”
Section: Induced Pluripotent Stem Cells Derived Neurons and The Dawn mentioning
confidence: 99%
“…Genomics studies showed that a portion of the genome from present-day humans outside Africa originates from an ancient admixture between modern humans and archaic humans. This admixture introduced Neanderthal and Denisovan alleles that are still present in humans today (Meyer et al, 2012;Prüfer et al, 2014;Slon et al, 2018) and that are carried on in human iPSCs derived from present day individuals (Dannemann et al, 2020) (Figure 2).…”
Section: Induced Pluripotent Stem Cells Derived Neurons and The Dawn mentioning
confidence: 99%